A solidariedade como prática curricular educativa - Mori, Katia Regina Gonçalves (2013)
This research analyzes solidarity as a curricular practice and aims to understand two particular points. First, the extent to which solidarity should be inherent to curricular practices and which are the activities that emphasize its teaching process. Secondly it seeks to contribute to the debate about the quality in education, which lately has been understood under two dichotomized functions: cognitive knowledge and preparing for citizenship. This is a research on qualitative analysis field and its theoretical framework is based upon the concepts of otherness (Levinas), ethics (Dussel), political commitment (Freire) and knowledge emancipation (Santos). The research took place in four schools of São Paulo metropolitan area, which represent the most important school systems (public, private and vocational schools). For data collection a questionnaire and semi-structured interviews were undertaken whose results were recorded and transcribed. The research informants were, educational coordinators, teachers and people from the community attended by schools under solidarity projects. This research allowed to realize that there is much variety in understanding how to develop pedagogical practices of solidarity, and this fact led to the development of a specific typology of solidarity practices in education: assistencialist; discursive; functional-participative; critical-emancipatory. This thesis seeks to contribute to the debate about the quality of education designed from the perspective of knowledge and solidarity as a fundamental value for the constitution of a society which wants to be plural and fair